Pengaruh Green Advertising, Packaging, dan Product terhadap Keputusan Pembelian dengan Kepuasan Pelanggan sebagai Variabel Mediasi (International Forum of Researchers and Lecturers, 2025)
This study aims to analyze the influence of green advertising, green packaging, and green product on the purchase decision of The Body Shop products, with customer satisfaction as an intervening variable. The background of this research is based on increasing consumer awareness of environmental issues, which drives changes in consumer preferences towards environmentally friendly products. Green marketing strategies are important in shaping a positive brand image and influencing consumer purchasing behavior. This study uses a quantitative approach with a path analysis method processed using SPSS software. The respondents in this study amounted to 100 students from the Faculty of Economics and Business, Wijaya Kusuma University Surabaya who had bought The Body Shop products. The results of the analysis show that green advertising, green packaging, and green products have a significant effect on customer satisfaction. Furthermore, green advertising and green products have also been shown to have a direct influence on consumer purchase decisions, while green packaging does not show a significant influence on direct purchase decisions. In addition, customer satisfaction has been shown to play a significant mediating variable in the relationship between green marketing variables and purchase decisions. These findings confirm that the implementation of green marketing strategies not only has a positive impact on the company's image and social responsibility, but also plays an important role in increasing customer satisfaction and encouraging consumers to make purchasing decisions. Therefore, companies are advised to continue to develop and integrate eco-friendly elements in their marketing strategies to increase competitiveness and consumer loyalty. This research also makes a theoretical contribution to the development of consumer behavior studies related to sustainable marketing, especially among the younger generation.